Comparison of shear behaviour of concrete beams reinforced with GFRP bars and steel bars. (September 2022) - Halvonik, Jaroslav; Borzovič, Viktor; Lániova, Dagmar
Abstract: This paper presents the results of an experimental program focused on a comparison of the shear behaviour of concrete beams reinforced by longitudinal GFRP bars and beams reinforced by ordinary steel reinforcement. Altogether, 24 tests were conducted on 12 beams reinforced with GFRP bars and 28 tests on 14 beams reinforced with steel reinforcement. The beams were subjected to three-point loading with shear slenderness of 3.0. An effect of axial stiffness of longitudinal reinforcement was examined. Six different reinforcement ratios, ranging from 1.34% to 7.44%, in the case of beams with GFRP bars and six reinforcement ratios ranging from 0.89 % to 2.38% in the case of beams with steel reinforcement were tested until its failure occurred. An effective depth of the beams of 100 mm was kept constant and beams were without any transverse reinforcement. The results show a favourable effect of the axial stiffness of the longitudinal reinforcement on the shear capacity in both cases. However, in the case of beams with GFRP bars, a better shear performance per unit increase of the axial stiffness was observed than in beams with steel bars. The experimental program revealed that the relation between the reinforcement ratio and the shear strength can be approximated by the cubic root of the ratio. A comparison of measured shear strengths with state-of-art design provisions for predicting shear capacity indicates good quality of all the considered models when the CoV of shear strength ratio V test / V model ranged from 0.079 to 0.109 in the case of beams with GFRP bars and from 0.062 to 0.110 in the beams with steel bars.